Chemical photoallergy: photobiochemical mechanisms, classification, and risk assessments. Issue 1 (January 2017) - Onoue, Satomi; Seto, Yoshiki; Sato, Hideyuki; Nishida, Hayato; Hirota, Morihiko; Ashikaga, Takao; Api, Anne Marie; Basketter, David; Tokura, Yoshiki
Abstract: Chemical photosensitivity can be elicited by exposure of the skin to various pharmaceutical substances, foods, cosmetics and other environmental chemicals, followed by exposure to sunlight. There are at least three types of chemical photosensitivity, i.e., photoirritancy (narrowly defined as phototoxicity), photogenotoxicity and photoallergenicity, and their clinical characteristics and mechanisms are quite different. Concerns about chemical photoallergy is increasing, and various studies have been made to clarify the photobiochemical characteristics of photoallergens and the mechanisms involved. Various methodologies, including in silico prediction models, photochemical assay systems, and in vitro phototoxicity prediction tools, have been developed to predict the photoallergenic potential of chemicals over the past few years. The aim of this manuscript is to review the clinical characteristics, pathogenetic mechanisms and photobiochemical features of photoallergens, with special emphasis on the current status about development of screening systems for predicting photoallergenic potential of chemicals.